Bulletin 77 The Electric Furnace in Metallurgical Work - Dorsey A. Lyon; JOSEPH F. CULLEN (The National Institute for Occupational Safety and Health (NIOSH), 1914)
In connection with its investigation looking to the prevention of waste and the increase of safety and efficiency in the mineral indus- tries the Bureau of Mines has undertaken a study of the possible uses of the electric furnace in metallurgy. This bulletin presents a com- pilation of such data as seem to be useful for the information of persons who may be interested in the matter. In the application of electricity to metallurgy three kinds of processes are involved, namely, mechanical, thermal, and electrolytic. Under the mechanical application of electricity come those proc- esses of dressing and concentrating ores that are known as either electrostatic or electromagnetic processes. In electrothermic processes the current is used as a source of heat. The fundamental differences between the various types of electric furnace that are at present in commercial use relate to the manner in which the electric current is applied, as may be noted by reference to that part of this report in which the subject is discussed. In electrolytic processes the electric current is used for depositing metals from solutions. The process may be conducted in one of the following ways: (1) The material to be treated may be put into solu- tion and then electrolyzed, the material thus treated forming the electrolyte; (2) the material to be treated may form the anode or be placed in contact with the anode; or (3) the material to be treated may form the cathode or be placed in contact with the cathode. This report treats of electrothermic processes, with the possible exception of those for the reduction of aluminum from its ores. Moreover, of the processes used in the so-called electrochemical in- dustries only those for the reduction of an ore to metal, or to a com- pound of the metal that is of value in itself, or is an aid in metallurgical work, are here discussed.